1990
DOI: 10.1121/1.399933
|View full text |Cite
|
Sign up to set email alerts
|

From touch to string vibrations. I: Timing in the grand piano action

Abstract: This article describes an experimental study of the timing in the grand piano action. The function of the action is described by timetables for the motions of the moving parts. Important timing properties included are the relation between key bottom contact and hammer–string contact, the interval of free hammer motion before the impact on the string, and the hammer–string contact duration. The influence of the regulation and dynamic level on these timing properties is analyzed. The results of the measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 0 publications
0
37
0
2
Order By: Relevance
“…Authors have suggested [2] that the pianistic touch lied precisely in this feature, which could seem insignificant at first sight. Therefore, we believe that discriminating different kinds of attacks could be possible if this flexible shank was part of our model and this is the object of a recent article [12].…”
Section: Conclusion and Prospectsmentioning
confidence: 98%
“…Authors have suggested [2] that the pianistic touch lied precisely in this feature, which could seem insignificant at first sight. Therefore, we believe that discriminating different kinds of attacks could be possible if this flexible shank was part of our model and this is the object of a recent article [12].…”
Section: Conclusion and Prospectsmentioning
confidence: 98%
“…The resistant force provided by the traditional piano action mechanism varies from 0.5 N (the minimum force that initiates key motion), to (at fortissimo nuance, according to [D. Parlitz, 1998]). Extensive measurements of the kinematics of a grand piano action mechanism [Askenfelt and Jansson, 1990] [Askenfelt and Jansson, 1991] indicate that the duration of the key motion varies from 20 to 250 ms depending on the nuance whereas the key velocity varies from 0.1 m.s -1 to 0.6 m.s -1 . We present here a system aimed at reproducing the dynamical behavior of the piano action.…”
Section: Haptic Interface For Musical Keyboardsmentioning
confidence: 99%
“…Wessel and Wright [36] for example, state a maximum latency of 10 ms between a stimulus and its response for control gestures and resulting sounds on a computer. However, in contrast Askenfelt und Janson [3] refer to an acceptable latency of up to 100 ms between the touch of a piano key and its hammer striking the string. Pneumatic pipe organs may even have latencies of several hundred milliseconds without affecting the musicians performance.…”
Section: Limitationsmentioning
confidence: 99%
“…Questions 1-8 were ranked on a 4-point Likert Scale: not at all (1), rudimentary (2), good (3), excellent (4). Questions 9 and 10 were ranked on a 5-point Likert Scale: very pleasant (1), pleasant (2), neutral (3), unpleasant (4), very unpleasant (5). For details regarding each specific question see Table 1.…”
Section: Questionnairementioning
confidence: 99%